10.2: Invited Paper: Development of Oxide TFT's Structures. Issue 1 (1st July 2013) - Bae, Jong UK; Kim, Dae Hwan; Kim, Kitae; Jung, Kiyoung; Shin, Woosup; Kang, Inbyeong; Yeo, SangDeog
Abstract Advanced structures of oxide TFT have been studied for various display applications. Oxide TFT with etch‐stopped layer has shown excellent uniformity and stability for display products. For mass production with low cost, however, back channel etched structure with/without titanium etch‐stopped one has been studied and demonstrated promising electrical properties comparable to etch stop structure. Furthermore, we have developed self‐aligned coplanar structure as one of ways to minimize parasitic capacitance and found excellent electrical properties and bias stability at 6 μm of channel length, which is demonstrated with 13.3 inch AMOLED.